(untitled) (New York, 2010)
With the fifteenth edition of Financial and Managerial Accounting: The Basis for Business Decisions, the Williams author team continues to be a solid foundation for students who are learning basic accounting concepts. In this revision, the authors have added to and refined the coverage of International Financial Reporting Standards (IFRS), particularly in Chapter 15 (“Global Business and Accounting”). Hallmarks of the text—including the solid Accounting Cycle Presentation, relevant pedagogy, and high quality, end-of-chapter material—have been updated throughout the book.
Keywords: Accounting,Managerial accounting,Quản trị kế toán,Kế toán